Avaliação da motivação e da aprendizagem em estudantes de medicina: Estudo comparativo entre aula tradicional contextualizada por discussão de casos clínicos e aula tradicional contextualizada por casos clínicos gamificados - Resende, Isabela Silveira de (2020)
Introduction: Gamification is the use of mechanisms based on video games, their design and elements of logic in order to engage and motivate people towards better learning and problem solving. Thus, one way to encourage engagement, group learning, collaboration and interaction is the use of educational games integrated into classes and seminars. Being part of a game encourages greater approximation to the learning aim, enabling the student to establish and apply the concepts that are being dealt with. As well as benefiting memory and performance, games and other interactive learning methods have important social benefits for the students. Aim: To assess the affects of adding gamification to traditional lessons that are contextualized through clinical case discussions for large groups of medical students. Methodology: This is an experimental study, given to 39 students from the third period of the medical school at the Presidente Tancredo de Almeida Neves University Center in São João Del Rei (MG), during the first semester of 2019. The same class was given to all the participants, dealing with the diagnostic differentials of Thyrotoxicosis and, following this, the sample was randomized into two groups: one group for clinical cases discussion and another for gamification of the clinical cases. At the end of the activities, assessment was made of student motivation, knowledge retention (short and long term) and knowledge transfer for the resolution of the Thyrotoxicosis clinical cases. Results: Analysis of the groups showed greater attention, confidence and satisfaction, among the motivation constructs, in the students that used the game compared with the students that were submitted to traditional clinical case discussion. Knowledge retention, in the short and long term, as well as knowledge transfer had similar levels between the two groups, showing that the educational game, in this context, is not inferior to the traditional method used. Conclusion: Therefore, the introduction of gamification, for learning reinforcement in traditional classes contextualized by clinical cases, may generate its own effects in increasing motivation in instructional activities